PENGGUNAAN KEMBALI BANGKAI BUS TRANSJAKARTA SEBAGAI MODUL PASAR PESING KONENG - Kristopher Henrico Ali; Franky Liauw (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Pesing Koneng Market is a wild market that has been operating in the Pesing area for a long time. In the past, the Pesing market managed to attract visitors from remote areas of Batavia. However, seeing its development which has given rise to various problems,  Urban Acupuncture strategy is needed to respond the degradation that occurs. Like a hermit crab changing its shell, the Pesing Koneng market that grows beyond its "shell" needs to find a new home for itself. Where the search for a new home or relocation strategy not only improves the market itself, but also affects the surroundings. Inspired by how the market community creatively reuses existing resources, this project seeks to bring these characteristics to a new site. Pesing Koneng market relocation site is close to the existing market. Where the site is a home of abandoned Transjakarta buses. By transfering the characteristics of the market, the reuse of abandoned transjakarta bus is done by breaking down the elements of the bus and using it as space, facilities, and entertainment in the market. This creates a different and unique market atmosphere in order to increase public interest in traditional markets. Keywords:  Market; Relocation; Reuse; Transjakarta Abstrak Pasar Pesing Koneng merupakan pasar liar yang sudah lama beroperasi di daerah pesing. Dahulu, pasar Pesing berhasil menarik pengunjung dari pelosok Batavia. Namun melihat perkembangannya yang memunculkan beragam masalah, diperlukan strategi Urban Acupuncture untuk merespon degradasi yang terjadi. Seperti kelomang yang mengganti cangkangnya, pasar Pesing Koneng yang tumbuh melebihi “cangkang”-nya perlu mencari rumah baru bagi dirinya. Di mana pencarian rumah baru atau strategi relokasi ini tidak hanya memperbaiki pasar itu sendiri, tetapi juga berpengaruh pada sekitarnya. Terinspirasi dari bagaimana masyarakat pasar secara kreatif menggunakan kembali sumber daya yang ada, proyek ini berusaha untuk membawa ciri khas tersebut pada tapak yang baru. Tapak relokasi pasar Pesing Koneng berada dekat dengan pasar eksisting. Di mana tapak tersebut merupakan rumah bagi bangkai bus Transjakarta yang terlantar. Dengan turut memindahkan karakteristik pasar, penggunaan kembali bangkai bus transjakarta dilakukan dengan memecah elemen bus dan menggunakannya sebagai ruang, fasilitas, hingga hiburan dalam pasar. Hal ini menciptakan suasana pasar yang berbeda dan unik demi meningkatkan minat masyarakat terhadap pasar tradisional.